Fabrication of advanced targets for laser driven nuclear fusion reactions through standard microelectronics technology approaches. (2nd October 2017) - Picciotto, A.; Crivellari, M.; Bellutti, P.; Barozzi, M.; Kucharik, M.; Krasa, J.; Swidlosky, A.; Malinowska, A.; Velyhan, A.; Ullschmied, J.; Margarone, D.
Abstract: Silicon targets enriched with hydrogen and doped with boron at high atomic concentration (10^{20} 20 –10^{22} 22 cm^{-3} −3 ) were designed and fabricated using ion implantation and thermal diffusion processes to be used for experiments in the field of laser driven nuclear fusion. Two main types of target were prepared: thin (2μ μ m) foils and thick (500μ μ m) slabs. Such targets were irradiated with a sub-nanosecond, kJ-class laser with a moderate intensity (\sim 10^{16} ∼ 10 16 W/cm^{2} 2 ) to trigger the p(^{11}\text{B}, α)2α ( 11 B, α)2α nuclear fusion reaction thanks to the acceleration of proton streams with energy of 0.1–1 MeV . The combination of the ad-hoc developed targets and the given laser pulse parameters allowed to generate a very high flux of alpha particles (10^{7} 7 –10^{9} 9 /sr per shot). The paper mainly focuses on microfabrication techniques and processes optimized for the fabrication of such advanced targets and on a comparison of the key results achieved with the different targets used in the experiment. Hydrodynamic simulations are also discussed.